2001
DOI: 10.4049/jimmunol.167.11.6217
|View full text |Cite
|
Sign up to set email alerts
|

Fas Ligand Engagement of Resident Peritoneal Macrophages In Vivo Induces Apoptosis and the Production of Neutrophil Chemotactic Factors

Abstract: Fas ligand (FasL) is a potent proapoptotic type-II transmembrane protein that can cause cell death in Fas+ target populations. Despite the presumed “silent” nature of apoptotic cell death, forced expression of FasL can induce a dramatic inflammatory response. To elucidate the in vivo mechanism(s) linking FasL and inflammation, we used a membrane-bound cell-free form of FasL (mFasL-vesicle preparation (VP)). We found that i.p. injection of FasL-microvesicles led to the rapid activation and subsequent demise of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
149
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(156 citation statements)
references
References 50 publications
6
149
1
Order By: Relevance
“…It has been reported that CD95L induces the processing and release of IL-1 g , which may be responsible for the infiltration by neutrophils [41]. CD95L may act on resident macrophages leading to increased production of IL-1 g and macrophage inflammatory proteins [42]. Moreover, engagement of CD95 on dendritic cells may induce the secretion of pro-inflammatory cytokines [43].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CD95L induces the processing and release of IL-1 g , which may be responsible for the infiltration by neutrophils [41]. CD95L may act on resident macrophages leading to increased production of IL-1 g and macrophage inflammatory proteins [42]. Moreover, engagement of CD95 on dendritic cells may induce the secretion of pro-inflammatory cytokines [43].…”
Section: Discussionmentioning
confidence: 99%
“…11,[39][40][41] These effector cells may directly kill Fas-expressing hepatocytes. 39 Alternatively, Fas-FasL crosslinking between innate immune cells and target cells such as hepatocytes, or even among the innate immune cells themselves within the liver, may have a pro-inflamamtory activity by inducing inflammatory cytokines/ chemokines, 11,[42][43][44][45] thereby aggravating APAP-induced liver injury. In the current study, we observed a marked reduction of FasL-expressing hepatic leukocytes in neutrophil-depleted mice compared with that in APAPtreated control mice, suggesting that neutrophils are important FasL-expressing cells in the liver and may contribute to APAP-induced liver injury through Fas/FasL pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The Fas/FasL-mediated apoptosis pathway has been implicated in immune response regulation (9,10), peripheral tolerance (5,(11)(12)(13)(14)(15), graft rejection (16 -18), tumor surveillance (19), tissue pathology (20 -22), chemotaxis (17,18,23), and maintenance of the immune privileged sites (24,25).…”
Section: F As (Cd95) Is a Type I Transmembrane Protein Expressed By Mmentioning
confidence: 99%